Managing Generation Y towards Organizational Excellence - Uduwawela, Shehani Romesha (2015)
The workforce today comprises of several distinctive generations working along together, with Generation Y (Gen Y) being the latest entry to the workplace. This latest entrance of employees has raised concern from organizations owing to their diverse work ethics, characteristics, and traits, which are significantly different to the previous generational cohorts. It is reported that Gen Ys enter the workforce with high expectations and are subjected to influence from varied factors that impact their productivity in the organization. Existing Human Resource (HR) practices seem to be in adequate to accommodate the Gen Y’s, needs and demands thus, has become a challenge to organizations in Sri Lanka to manage them towards organizational excellence. The aim of this study is to examine the organizational environmental factors that affect Gen Y and their contribution towards organizational excellence. The organizational environmental factors that influence Gen Y include Internal Influences, External Influences, and finally Gen Y Attributes. The factors that impact managing Gen Y include organization corporate strategy, organization HR policies that fall under internal influences; political, economic, social, technological, legal, and environmental, that fall under external influences; and lastly, work values, attitude, behavior, and work culture that falls under Gen Y attributes. This study found that all three factors had a significant influence on Gen Ys that in turn impacted organizational excellence in Sri Lankan organizations. Overall, there appears to be a gap between the Gen Y’s expectations and the Sri Lankan organization’s current HR practices. Hence, HR managers are advised to modify their HR practices in order to accommodate the Gen Ys in order to manage them more effectively towards organizational excellence. This can be achieved by; incorporating Gen Ys in the corporate strategy, providing innovative methods of training and development, encouraging mentor-mentee relationships, introducing competitive reward packages, providing up-to-date technology, creating a flexible working environment and creating a Gen Y friendly work culture.